Tender Care": Iranian Women's Needs to Cope with Hysterectomy and Oophorectomy- A Qualitative Content Analysis Study - Omsalimeh Roudi; Batool Tirgari; Mohammad Ali Cheraghi; Nahid Dehghan Nayeri; Masoud Rayyani (Shiraz University of Medical Sciences, 2019)
Background: Gynecological surgeries associated with loss of feminine organs evoke more personal, interpersonal and psychological distress that may diminish women's quality of life. Women need and seek support to cope with various distresses which may change over the course of diagnosis to treatment. This study aimed to explore Iranian women's needs to cope with hysterectomy and oophorectomy. Methods: This qualitative study was conducted in Kerman and Tehran, Iran from 2015 to 2017. Thirty interviews were conducted with 28 eligible participants including 24 main participants including one gynecologist, one midwife and one nursing faculty member, one gynecologist and one midwife and 2 husbands. They were recruited through purposeful sampling. Data were collected through semi-structured and in-depth interviews and analyzed with Graneheim and Lundman's method of conventional content analysis. The trial version of the MAX QDA 10 Software was used to manage the coding process. Results: "Tender care" emerged as the main theme. It was comprised of three categories: "to be well-informed, "to be treated with compassion in healthcare setting", and "to be welcomed in the society". Conclusion: Women after hysterectomy/oophorectomy were preoccupied with many physical and emotional concerns. They need a whole package of care which consists of proper information to know what to do, a well-prepared/trained healthcare setting to meet their needs, and visibility in the society as a whole person. A multidisciplinary approach must be activated to meet their coping requirements and it is necessary to address these needs in each level of healthcare services.